Facile synthesis of 3D hierarchical N-doped graphene nanosheet/cobalt encapsulated carbon nanotubes for high energy density asymmetric supercapacitors. Issue 24 (3rd June 2016) - Balamurugan, Jayaraman; Thanh, Tran Duy; Kim, Nam Hoon; Lee, Joong Hee
Abstract : The 3D NG/Co–NCNT based asymmetric supercapacitors provide high energy density ( 88.44 W h kg −1 ), an ultra-high power density ( 17 991 W kg −1 at 56.97 W h kg −1 ), and outstanding stability ( 10 000 times). Abstract : A novel three-dimensional (3D) hierarchical hybrid architecture, consisting of in situ designed cobalt-encapsulated nitrogen doped carbon nanotubes (Co–NCNTs) grown on nitrogen doped graphene (NG), is fabricated for asymmetric supercapacitors. When evaluated as an electrode material for supercapacitors, the 3D hybrid has an excellent energy density, outstanding rate capability and long-cycle life compared with commercial electrode materials. The decent electrochemical performance is comparable to most of the earlier reported results and the synergistic effect boosts the pseudocapacitive performance. The constructed hybrid exhibits excellent energy storage characteristics, which result in an ultra-high specific capacitance of 2568 F g −1 at 2 A g −1 and excellent rate capability with an extraordinary capacitance of 1594 F g −1 at 100 A g −1 (96.64% capacitance retention after 20 000 cycles). The improvement in the outstanding electrochemical performance can be attributed to the unique morphology, extraordinary porosity, excellent conductive networks, and the intense networking of Co–NCNT and NG nanosheets in the 3D hybrid. An asymmetric supercapacitor fabricated using the 3D NG/Co–NCNT hybrid as the positive electrode and NG as the negative electrode demonstrates exceptional performance for practical energy storage devices. The assembled asymmetric supercapacitors provide a greater energy density (∼88.44 W h kg −1 ), an ultra-high power density (∼17 991 W kg −1 at 56.97 W h kg −1 ), and outstanding cyclability (∼10 000 times).